Totally Implantable Venous Access Devices: A Review of Complications and Management Strategies. (February 2017) - Tabatabaie, Omidreza; Kasumova, Gyulnara G.; Eskander, Mariam F.; Critchlow, Jonathan F.; Tawa, Nicholas E.; Tseng, Jennifer F.
Abstract : Objective: Totally implantable venous access devices (portacaths, or "ports"), are widely used for intermittent central venous access especially for cancer patients. Although ports have a superior safety margin compared with other long-term venous access devices, there are a number of complications associated with their use. Methods: This is a narrative review. We searched PubMed and Google Scholar for articles about complications related to the use of portacaths. "Similar articles" feature of PubMed and reference list of the existing literature were also reviewed for additional relevant studies. Results: In this review, we provide the latest evidence regarding the most common ones of these adverse events and how to diagnose and treat them. Immediate complications including pneumothorax, hemothorax, arterial puncture, and air embolism as well as late complications such as port infection, malfunction, and thrombosis are covered in detail. Conclusions: Physicians should be familiar with port complications and their diagnosis and management.